Kant's Provisionality Thesis. Issue 3 (September 2019) - MESSINA, J. P.
Abstract: I argue that Kant's mature political philosophy entails the provisionality thesis. The provisionality thesis asserts that in a world like ours, populated with beings sufficiently like us, acquired rights (rights to external objects of choice, including property, sovereignty and territory) are necessarily provisional. I motivate the standard view, which restricts the notion of provisional right to the state of nature and the transition from the state of nature to the civil condition. I then provide two textual arguments against it. I conclude by reflecting on the normative implications of the provisionality thesis, arguing that they are more modest than has been formerly appreciated.